No need to be rebellious: placemaking and value co-creation in the skateboarding City of Malmö - Book, Karin (Frontiers in Sports and Active Living, 2024)
During the last 20 years, Malmö has developed into an internationally recognised skateboarding destination and a valued skateboarding place for local and regional skaters. In contrast to many cities, skateboarding and skateboarders have been appreciated and embraced in public planning and development. The aim of the paper is to discuss the development and identity of Malmö as a skateboarding city through the lens of the concepts of placemaking and value co-creation, and—not least—through the narratives of six persons with different relations to skateboarding and Malmö. The paper shows that the City of Malmö has engaged with local skateboarding communities through several initiatives that have fostered a collaborative relationship. The non-profit association Bryggeriet, a skateboard high school, an active skateboarding community, and the City of Malmö are all involved in the placemaking and co-creation of Malmö as a skateboarding city. The city's approach to skateboarding involves a bottom-up strategy, engaging non-experts in the development of spaces, reflecting a shift from traditional top-down models towards a co-creation model in order to create synergetic outcomes. Malmö's transformation into a skateboarding city is characterised by the integration of skateboarding into the urban fabric, showcasing a welcoming attitude. The paper underscores the dynamic interplay between physical, imagined, and lived spaces in urban skateboarding culture. However, it also demonstrates how a successful and professionalised model for introducing the skateboarders’ interests into the corridors of power risks undermining the link to, and the engagement of, the new generation of grassroots skaters, and maybe also the edgy, rebellious character of skateboarding.